The Perfection of Religion in the Qur’an: QS AlMā’idah verse 3 in the view of Ibnu ‘Abbas and Hamka’s Interpretation - Amalina Setiani; Muhammad Labib Syauqi (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Islam was comprehensive for all human races, in all areas of their lives, and whenever they live until the Judgment Day is coming. This is what is commonly called as Islam is universal. When The Prophet Muhammad SAW was performing of Hajj Wadā’ came down the al-Mā’idah verse: 3 has become an argument for some Muslims to show that Islam is perfect. In this time, many cases of a wrong understanding of religion's perfection will cause problems such as radicalism, disbelief of other groups, and even terrorism. Therefore, the writer used two problem statements: how is the interpretation of religion perfection in QS. al-Mā’idah : 3 according to Tafsīr Ibnu ‘Abbās and Tafsir Al-Azhar then how is the relevance of Ibnu ‘Abbas and Hamka’s interpretation related to the perfection of religion with the Indonesian context. The method used by the writer in this research is library research with descriptive analysis and used philosophical hermeneutics by Hans Georg Gadamer. Then, the writer concluded The meaning perfection of religion in QS. al-Mā’idah : 3 according to Ibnu ‘Abbas in Tafsīr Ibnu ‘Abbās which is Allah SWT has perfected the faith of the Prophet Muhammad and the believers, there is no need for additions and no deductions for eternity. According to Hamka in Tafsir Al-Azhar, the perfection of religion is the creed, worship, syariat, muamalah, and munakahat was sufficient and there will be no additional. However, Hamka allows for ijtihad in matters other than worship and syariat. Therefore, Islam does not freeze. Then, in Indonesia context that consists of various tribes, languages, cultures, and religions. Therefore, the meaning of surrender to God can be reflected in Indonesia. Because all religions also teach surrender to God or in other words “kalimatun sawā’”. Suppose someone has a resigned attitude to God. In that case, it will minimize fanaticism, claiming the truth of his religion, insulting other groups who disagree with their perception, the narrow meaning of jihad and the blasphemy of religion, even radicalism, because someone considers that in other religions there is also faith. However, change is greatly affected by time and space. In terms of religions, that is permanent, and some are changing or normative Islam and historical Islam. By having an attitude of surrender to God, it is possible to happen tolerant to other religions. In brief, Indonesia can still be a country with the slogan “Bhineka Tunggal Ika” which means “unity in diversity”.